Enhanced photocatalytic degradation of tetracycline hydrochloride by novel porous hollow cube ZnFe2O4 - Cao, Yang; Lei, Xianyu; Chen, Qianlin; Kang, Chao; Li, Wenxue; Liu, Baojun (Journal of photochemistry and photobiology. A, Chemistry., 2018)
[Display omitted] •The porous hollow cube ZnFe2O4 exhibits excellent photocatalytic activity for degradation of tetracycline hydrochloride under visible-light.•UUsing PB as the MOF precursor synthesized ZnFe2O4.•The prepared ZnFe2O4 was cubic and had porous hollow structure.•Holes and electrons of the porous hollow cube ZnFe2O4 were efficiently separated. As a broad-spectrum antibacterial agent, tetracycline hydrochloride (TCHC) was widely used in medical treatment and animal husbandry. However, the TCHC in various systems such as the soil, rivers and foods, had caused great harm to the environment and human health. Among the many methods for treated tetracycline hydrochloride in wastewater, the photocatalytic treatment had great advantages. In this study, we used Prussian blue as a precursor to synthesized porous hollow spinel cube ZnFe2O4 for photocatalysis. The experimental results showed that the degradation rates of the prepared porous hollow cube ZnFe2O4 (l-ZnFe2O4) significantly better than the commercially available ZnFe2O4 (g-ZnFe2O4) and the ZnFe2O4 prepared by the coprecipitation method (p-ZnFe2O4). In addition, we made a further introduction on the degradation mechanism of TCHC. The porous hollow cube ZnFe2O4 could be expected to provide a green and effective for material degradation of tetracycline hydrochloride in water.